Class and Social Inequalities in Portugal: From Class Structure to Working-Class Practices on the Shop Floor - Estanque, Elísio (2004)
This paper addresses the emergence and development of class analysis in Portugal. Starting with a reference to the process of institutionalising sociology, I will discuss the influence of different schools of thought in the light of the political context, i.e. the 1970s, in which social class theories and Portuguese sociology itself were born. I will refer to different theoretical and methodological perspectives, and, in particular, discuss the interconnections between quantitative and qualitative approaches, while emphasising the advantages of the latter. These will be illustrated with examples of my own research based on the participant observation method, showing some aspects of daily life on the shop floor where I worked. Finally, I will propose some new lines and prospects for future developments in research into social inequality.